Sejarah Munculnya Syiah dan Perkembangannya di Dunia Islam - Fikar, Zulfikar; Santalia, Indo (CV Kalimasada Group, 2024)
In general, Shia is defined as helping followers, defending an idea or someone. In the modern sense, the word Shi'a is used to describe a group of Muslims who saved Ali ibn Abi Talib in particular with great fanaticism. Regarding the emergence of the Shia, historians have different opinions, some say that its emergence occurred after the death of the Prophet Muhammad. At the time of the election of Muslim leaders, another opinion said that the beginning of its emergence was at the end of Ustman bin Affan's caliphate at the beginning of Ali bin Abi Talib's caliphate. The popular opinion is that Shia emerged when negotiations failed between Caliph Ali bin Abi Thakib and the rebels, namely Muawiyah bin Abu Sufyan's troops during the Shiffin war. This research aims to reveal the history of the emergence of Shia and its development in the Islamic world by using a bibliographic research approach. There are several groups of Shiites, including Zaidiyah Shiites, Itsna 'Asyariyah Shiites, namely Shiites who believe in the twelve Imams, Ar-Rafidah Shiites, namely the group addressed to the attitude of supporters of the Ahlul Bait, the indifferent attitude of Abu Bakar Umar and most of the Prophet's friends.